Aktivitas Sediaan Gel Ekstrak Batang Pohon Pisang Ambon dalam Proses Penyembuhan Luka pada Mencit - Febram Prasetyo, Bayu; Wientarsih, Ietje; Pontjo Priosoeryanto, Bambang (Jurnal Veteriner; Vol 11 No 2 (2010), 2010)
The purpose of this study is to examine the activity of Ambon banana extract in gel formulation on thewound healing process of mice skin (Mus musculus albinus) based on gross and microscopic observations.The wound healing process were observe grossly everyday while the microscopic lesion was observed on the3rd, 5th, 7th, 14th and 21st days after skin incisition. The wounded skin were sampled after the mice wereeuthanized for further microscopic observation. The gross parameters were the existence of blood coagulation,scab formation, wound covering and wound size. The microscopic parameters observed the percentation ofwound reepitelization and the the tickness of wound connective tissues (fibroblast). Gross lesion and thefibroblast thickness were presented descriptively as a qualitative data. Grossly, it was observed that thescab formation was faster in mice treated with the extract of ambon banana than that of negative control.Based on the research the ambon banana extrack in gel can be used in the acceleratiof wound healing.
Keywords: gel , Ambon Banana extract, wound healing, mice